Supercapacitor markets, technology roadmap, opportunities 2021-2041 : ultracapacitor, EDLC, LIC, energy storage, battery replacement, vehicles, trains, aerospace, military, medical, marine, energy sector, microgrid, UPS, IOT, energy harvesting, electronics /: ultracapacitor, EDLC, LIC, energy storage, battery replacement, vehicles, trains, aerospace, military, medical, marine, energy sector, microgrid, UPS, IOT, energy harvesting, electronics. ([2020?]) - Harrop, Peter
No abstract available